Higher Order Series Resonant Dc-Dc Converter For High Voltage Applications - Amir, Asim (2014)
The conventional series resonant High Voltage (HV) DC-DC converter power supply is able to absorb the leakage inductance of the HV transformer, provides lower component stress and prevents the HV transformer from being saturated but poses poor controllability at light load and lower efficiency. To overcome these problems, this research work proposes higher order resonant topologies of series resonant HV DC-DC converter with two different output voltage control strategies. A fourth order LCCL series resonant HV DC-DC converter was designed consisting of four storage elements; a capacitor connected in parallel with a linear variable inductor (LVI) and the leakage inductance of the HV transformer in series. Two control strategies are proposed to regulate the output voltage of the LCCL series resonant HV DC-DC converter. First control strategy, is based on varying the switching frequency while keeping the resonant frequency constant. In the second control strategy, the switching frequency is kept constant while the output voltage control is achieved by varying the resonant inductance. This is accomplished by using a LVI in the tank circuit. Operation of the converter is carried out in continuous conduction mode. Both control schemes which are implemented to the LCCL series resonant based HV DC-DC converter show the capability to produce high output voltage at 75% efficiency for input power of 18 W. The result is verified for both simulation and experimental setup.